The Budget and the Bedroom: Associations between Financial Management Behaviors, Perceptions of Economic Pressure, and Sexual Satisfaction - Matthew T. Saxey; Chelom E. Leavitt; Jeffrey P. Dew; Jeremy B. Yorgason; Erin K Holmes; Ashley B. LeBaron-Black (Journal of Financial Therapy, 2021)
Although money and sex are both salient to romantic relationships, previous literature has rarely examined the association between the two. In the current study, we evaluate associations between financial management behaviors, perceptions of economic pressure, and sexual satisfaction. We used nationally representative opposite-sex newlywed dyadic data (N = 1,447 couples) and an actor-partner interdependent structural equation model to test these associations. Results indicate that as financial therapists aid opposite-sex newlywed clients in their financial management, they may also be lessening perceptions of economic pressure. For wives, this lessening of perceptions of economic pressure may benefit husbands’ and wives’ sexual satisfaction. Financial therapists may consider using these findings to encourage opposite-sex newlywed clients to practice healthy financial management behaviors and communicate about finances and sex. In short, our findings suggest that for opposite-sex newlywed couples, the budget may have something to do with the bedroom.
Keywords: financial management behaviors; sexual satisfaction; economic pressure; financial stress